PENGEMBANGAN BAHAN BACAAN REFUTATION TEXT SEBAGAI MEDIA UNTUK MEREMEDIASI MISKONSEPSI MATERI MOMENTUM DAN IMPULS - Yulia, Yulia; Maria Silitonga, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze and produce refutation-structured text handout to remediate student misconception on momentum and impulse. Research and Development (R&D) method used in this study which is adopted from seven steps Borg & Gall development. It involved 89 students from 3 schools in Pontianak and Kubu Raya whom participated in preliminary field and main field. Data collected by using validity questionnaire, student response questionnaire and diagnositc test. The result shows refutation-structure text handout has valid categories which are it can be seen from content feasibility 0,852 (very high criteria), presentation 0,821 (very high criteria), language 96,67% (very good category) and graphic 81,67% (good category). Students response on preliminary field and main field, respectively 81,30% (very high category) and 82,73% (very high category). The results of this study was expected could be used by teacher to remediate momentum and impulse misconception as an alternative media.Â Keyword: Development, Refutation-Structured Text Handout, Momentum and Impulse